Atrial cardiomyopathy markers predict ischemic cerebrovascular events independent of atrial fibrillation in patients with acute myocardial infarction - Li, Zhitong; Wang, Xin; Liu, Quanbo; Li, Chenglin; Gao, Jinghan; Yang, Yiheng; Wang, Binhao; Hidru, Tesfaldet H.; Liu, Fei; Yang, Xiaolei; Xia, Yunlong (Frontiers in Cardiovascular Medicine, 2022)
Background Contemporary data on atrial cardiomyopathy (ACM) markers and ischemic cerebrovascular events (ICVE) in patients with acute myocardial infarction (AMI) is lacking. We aimed to examine whether ACM markers predict ICVE among AMI patients. Materials and methods A total of 4,206 AMI cases diagnosed in clinical examinations between January 2016 and June 2021 were assessed for markers of ACM including B-type natriuretic peptide (BNP), P-wave terminal force in ECG lead V1 (PTFV1), and left atrium diameter (LAD). Left atrial enlargement (LAE) and abnormal PTFV1 were defined by previously published cut-off points. The primary outcome was incident ICVE composed of ischemic stroke (IS) and transient ischemic attack (TIA). Receiver operating curve analyses were used to compare the predictive performance of the CHA2DS2-VASc score combined with ACM markers to the CHA2DS2-VASc score alone. Results During a median follow-up of 44.0 months, 229 (5.44%) ICVE occurred. Of these, 156 individuals developed IS and the remaining 73 cases were diagnosed with TIAs. The ICVE group showed larger PTFV1 and increased LAD as well as elevated BNP levels at baseline. In the multivariate analysis, we found significant associations with ICVE for PTFV1 (HR per 1,000 μV*ms, 1.143; 95% CI, 1.093–1.196), LAD (HR per millimeter, 1.148; 95% CI, 1.107–1.190), but not BNP after adjusting for known ICVE risk factors and interim atrial fibrillation (AF). The addition of abnormal PTFV1 and LAE improved the predictive accuracy of the CHA2DS2-VASc score with C-statistic increasing from 0.708 to 0.761 (p < 0.001). Conclusion Atrial cardiomyopathy markers including PTFV1 and LAD were associated with incident ICVE independent of well-established risk factors and AF occurrence. The addition of ACM markers with CHA2DS2-VASc score may well discriminate individuals at high risk of ICVE in AMI patients.